2016
DOI: 10.1063/1.4955222
|View full text |Cite
|
Sign up to set email alerts
|

Electro-absorption of silicene and bilayer graphene quantum dots

Abstract: To cite this version:Hazem Abdelsalam, Mohamed Talaat, Igor Lukyanchuk, M. Portnoi, V. Saroka. Electro-absorption of silicene and bilayer graphene quantum dots. Journal of Applied Physics, American Institute of Physics, 2016, 120 (1) We study numerically the optical properties of low-buckled silicene and AB-stacked bilayer graphene quantum dots subjected to an external electric field, which is normal to their surface. Within the tight-binding model, the optical absorption is calculated for quantum dots, of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 47 publications
0
29
0
Order By: Relevance
“…These states are absent in graphene dots of similar shape and are attributed to the puckered structure of phosphorene. Similar states exist only in triangular graphene and silicene counterparts with zigzag edges [42,72]. We found that for each type of phosphorene dot with regular edges the number of these peculiar states is related to the dot size indexed by the number of hexagonal elements at one edge, see Table III.…”
Section: Discussionmentioning
confidence: 63%
“…These states are absent in graphene dots of similar shape and are attributed to the puckered structure of phosphorene. Similar states exist only in triangular graphene and silicene counterparts with zigzag edges [42,72]. We found that for each type of phosphorene dot with regular edges the number of these peculiar states is related to the dot size indexed by the number of hexagonal elements at one edge, see Table III.…”
Section: Discussionmentioning
confidence: 63%
“…ZES appear in triangle GQDs while DES appear in other shapes such as hexagonal and circular GQDs. Due to the inclusion of electron-electron interactions in the density functional theory (DFT) calculations, a tiny energy gap is opened between ZES [2,6,9]. In general, TB or DFT calculations confirmed the appearance of edge states in GQDs.…”
Section: -Introductionmentioning
confidence: 99%
“…Flake-like graphene quantum dots (GQDs) have attracted great attention due to their unique electronic [1][2][3][4][5] and optical [6][7][8][9][10] properties. The distinguishable properties of GQDs arise from the electron confinement in the finite size graphene cluster that leads to the opening of energy gap and quantization of electronic energy levels.…”
Section: -Introductionmentioning
confidence: 99%
“…In what follows we consider only quasi-metallic AGNRs, for which the edge effects lead to more prominent interband transitions between the closest valence and conduction subbands than for ZGNRs [16](triangular bilayer graphene clusters with zigzag edges also have weak interband transitions between the edge states [17]). The band structure of AGNRs can be obtained from that of graphene by a technique similar to that used for dealing with CNTs.…”
Section: Graphene Nanoribbonsmentioning
confidence: 99%